Assessment of lower limb neuromuscular control in prepubescent athletes - Barber-Westin, S. D.; Galloway, M.; Noyes, F. R.; Corbett, G.; Walsh, C. (The American Journal of Sports Medicine, 2005)
Background: Although neuromuscular indices have been extensively studied in adolescents and adults, limited data exist for prepubescent children.